PREVALENCE OF DEPRESSION AND ASSOCIATED FACTORS AMONG MIDDLE-AGED WOMEN IN VAN GIANG DISTRICT, HUNG YEN PROVINCE, 2023 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence of depression among middle-aged women and to analyze factors associated with depressive disorder in Van Giang district, Hung Yen province, 2023.Subjects and methods: A cross-sectional descriptive study was conducted among 412 middle-aged women aged 40–59 years in Van Giang district, Hung Yen province. Data were collected through face-to-face interviews at participants’ homes using a structured questionnaire.Results: The prevalence of depressive disorder among middle-aged women was 28.9%. Depression was significantly associated with marital status, economic condition, risk factors, alcohol use, menopausal symptoms, family history of depression, level of social/family/community support, and chronic diseases.Conclusion: Depression was significantly associated with marital status, alcohol use, family history of depression, menopausal symptoms, and chronic conditions, while social support played a protective role. No association was found with age group or place of residence.
Keywords: Depressive disorder; Middle-aged women; PHQ-9.